Synthesis and biological evaluation of new pyrazolone Schiff bases as monoamine oxidase and cholinesterase inhibitors - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
In the current work, Schiff base derivatives of antipyrine were synthesized. The chemical characterization of the compounds was confirmed using IR, H-1 NMR, C-13 NMR and mass spectroscopies. The inhibitory potency of synthesized compounds was investigated towards acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), and monoamine oxidases A and B (MAO-A and MAO-B) enzymes. Some of the compounds displayed significant inhibitory activity against AChE and MAO-B enzymes, respectively. According to AChE enzyme inhibition assay, compounds 3e and 3g were found as the most potent derivatives with IC50 values of 0.285 mu M and 0.057 mu M, respectively. Also, compounds 3a (IC50 = 0.114 mu M), 3h (IC50 = 0.049 mu M), and 3i (IC50 = 0.054 mu M) were the most active derivatives against MAO-B enzyme activity. So as to understand inhibition type, enzyme kinetics studies were carried out. Furthermore, molecular docking studies were performed to define and evaluate the interaction mechanism between compounds 3g and 3h and related enzymes. ADME (Absorption, Distribution, Metabolism, and Excretion) and BBB (Blood, Brain, Barier) permeability predictions were applied to estimate pharmacokinetic profiles of synthesized compounds.
Keywords: Schiff base; Acetylcholinesterase; Butyrylcholinesterase; Monoamine oxidase A; Monoamine oxidase B; Docking; ACETYLCHOLINESTERASE INHIBITORS; DERIVATIVES; ANALOGS; SOLUBILITY